Activation of peroxymonosulfate by BiOCl@Fe3O4 catalyst for the degradation of atenolol: Kinetics, parameters, products and mechanism. (February 2019) - Wu, Yanlin; Fang, Zhongyi; Shi, Yahong; Chen, Hongche; Liu, Yankun; Wang, Yifan; Dong, Wenbo
Abstract: BiOCl@Fe3 O4 photocatalyst was synthesized to activate peroxymonosulfate (PMS) for atenolol (ATL) degradation under simulated sunlight irradiation in present study. XRD, SEM, adsorbability and pore size distribution of BiOCl@Fe3 O4 were analyzed. Magnetic BiOCl performed high activity in PMS activation and could be easily solid-liquid separation by applying an external magnetic field. Many parameters were inspected, including scavengers, PMS concentration, catalyst dosage, pH, anions (Cl − and CO3 − ). h +, SO4 −, HO, O2 −, SO5 − were involved in ATL degradation in BiOCl@Fe3 O4 /PMS/sunlight system. The second-order rate constant of the reaction between ATL and SO4 − ( k ATL, SO4 − ) was estimated via laser flash photolysis experiments. Moreover, ATL mineralization was followed by TOC analyzer. Twelve possible intermediate products were identified through LC-QTOF-MS analysis, and six ATL degradation pathways were concluded. This type of magnetic photocatalyst is characterized by ease of separation, high activation and good reusability. It may have application potential in refractory organic pollutants degradation. Graphical abstract: Highlights: ATL was degraded efficiently by sunlight/BiOCl@Fe3 O4 /PMS system. The second-order rate constants ( k ATL, SO4- ) was measured. Radical species contributed to ATL degradation was investigated. The applied pH range was expanded from acid to neutrality. Effect of chloride and carbonate ions was assessed.